They don't come with instructions : cries, wisdom, and hope for parenting children with developmental challenges - Holt-Woehl, Hollie M. (Fortress Press, 2018)
Hollie M. Holt-Woehl offers insights for the journey with a developmentally challenged child. As the mother of a son with an autism diagnosis, she also offers ways to keep hope. The book focuses on the challenges of parenting children with Autism Spectrum Disorder (ASD), Attention-Deficit/Hyperactivity Disorder (ADD/ADHD), and/or Fetal Alcohol Syndrome (FAS). Readers who seek to understand what it is like to live with a developmentally challenged child will appreciate Holt-Woehl's down-to-earth and compassionate approach.